Turnerjeva ustanova - fundacija - Trstenjak, Verica (Studia Historica Slovenica, 2001)
The authoress, in the paper, deals with the activity of Dr. Pavel Turner in the area of charity, i. e. as a patron of arts, philanthropist. Dr. Pavel Turner devoted his entire estate, real estate and movables to a special institution titled: The Institution of Dr. Pavle Turner for the Up-Grading of Professional and World Education for Graduated Slovene Jurists and Philosophers. It was established by his will in 1924, and it was constructed as a legal entity. It enabled post-graduate, i. e. post-doctoral studies to numerous jurists and philosophers. Institutions are lasting as a rule, whereas Turner's ceased to exist at the alteration of various historical periods. It is possible that it recommences to exist within the process of denationalisation and the return of the estate
Keywords: biografije; fundacije; izobraženci; kulturna zgodovina; mecenstvo; skladi; slovenska inteligenca; Turner, Pavel